Economic analysis of the cocoa sector in Norte de Santander State, Colombia and at an international level - Vásquez-Barajas, Eduardo Felipe; García-Torres, Nelson Emilio; Bastos-Osorio, Liliana Marcela; Lázaro-Pacheco, Joordan Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The main objective is to analyze economically the cocoa sector in Norte de Santander State, in Colombia and at an international level. The method is deductive with a descriptive and a field research, besides some databases such as Colombian and international cocoa institutions were consulted as well as documentary sources of state and private organizations. In terms of results and conclusions, Norte de Santander State and Colombia need to increase cocoa production, to promote the crop’s technification to take advantage of the high international demand for cocoa and its by-products, as well as the good prices for extending the international participation, considering the differential advantage with its fine flavour and aroma. Therefore, it is necessary to generate an added value, competitiveness; to use the advantages of the active free trade agreements in Colombia and the projection of cocoa as a key crop of the Colombian post-conflict.